Ultra-fast speech comprehension in blind subjects engages primary visual cortex, fusiform gyrus, and pulvinar - a functional magnetic resonance imaging (fMRI) study. - Dietrich, Susanne; Hertrich, Ingo; Ackermann, Hermann (BMC Neuroscience, 2013)
Background: Individuals suffering from vision loss of a peripheral origin may learn to understand spoken language at a rate of up to about 22 syllables (syl) per second - exceeding by far the maximum performance level of normal-sighted listeners (ca. 8 syl/s). To further elucidate the brain mechanisms underlying this extraordinary skill, functional magnetic resonance imaging (fMRI) was performed in blind subjects of varying ultra-fast speech comprehension capabilities and sighted individuals while listening to sentence utterances of a moderately fast (8 syl/s) or ultra-fast (16 syl/s) syllabic rate.Results: Besides left inferior frontal gyrus (IFG), bilateral posterior superior temporal sulcus (pSTS) and left supplementary motor area (SMA), blind people highly proficient in ultra-fast speech perception showed significant hemodynamic activation of right-hemispheric primary visual cortex (V1), contralateral fusiform gyrus (FG), and bilateral pulvinar (Pv).Conclusions: Presumably, FG supports the left-hemispheric perisylvian "language network", i.e., IFG and superior temporal lobe, during the (segmental) sequencing of verbal utterances whereas the collaboration of bilateral pulvinar, right auditory cortex, and ipsilateral V1 implements a signal-driven timing mechanism related to syllabic (suprasegmental) modulation of the speech signal. These data structures, conveyed via left SMA to the perisylvian "language zones", might facilitate - under time-critical conditions - the consolidation of linguistic information at the level of verbal working memory.